2013
DOI: 10.1136/bmjopen-2013-002578
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic surgical training following modernising medical careers: regional variation in experience across the UK

Abstract: ObjectivesTo evaluate surgical experience among current doctors appointed into ophthalmology training posts since the introduction of the Modernising Medical Careers programme. Additionally, to identify regional variations in surgical experience and training programme delivery.DesignA cross-sectional survey.SettingThe UK's four largest deaneries (Schools of Ophthalmology).ParticipantsTrainee ophthalmologists, all having completed three or more years of training, who were appointed to the new ophthalmic special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 11 publications
(11 reference statements)
0
22
0
Order By: Relevance
“…Changes in educational theory34 and the European Working Time Directive35 have limited training opportunities for ophthalmologists-in-training. As a result, procedures such as trabeculectomy feature less often in trainees’ timetabled clinical activity 36. Work-hour restrictions and a demise of the ‘mentor’ model in medical training may have damaging consequences for acquisition of technical skills and surgical resilience 37.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in educational theory34 and the European Working Time Directive35 have limited training opportunities for ophthalmologists-in-training. As a result, procedures such as trabeculectomy feature less often in trainees’ timetabled clinical activity 36. Work-hour restrictions and a demise of the ‘mentor’ model in medical training may have damaging consequences for acquisition of technical skills and surgical resilience 37.…”
Section: Discussionmentioning
confidence: 99%
“…There is an assertion that the number of cases undertaken by trainees has fallen over time. This has been attributed to (among other reasons) organisational and political changes such as the European Working Time Directive . England reported that trainees undertook around 1000 cases per year in 1990, but by 1999, this figure had dropped to 500 with this downward trend persisting .…”
Section: Discussionmentioning
confidence: 99%
“…Minimum competencies are specified in the training curriculum that is maintained by the RCoA . However, experience accrued during the course of postgraduate specialty training is thought to vary across geographical regions . In recent years, training in anaesthesia has undergone significant change.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Some units have moved towards training and non-training lists. 11 , 22 , 23 This has its own challenges in terms of how patients give consent. In terms of risk factors for cataract surgery (eg, very old age, myopia, advanced hypermetropia, deep brow, pseudoexfoliation, etc) very few patients presented with these features (range of 0.2%–1.5%).…”
Section: Discussionmentioning
confidence: 99%